Coronary reperfusion and clinical outcomes after thrombus aspiration during primary percutaneous coronary intervention: Findings from the HORIZONS‐AMI trial. Issue 4 (26th June 2013) - Nilsen, Dennis W.T.; Mehran, Roxana; Wu, Roland S.; Yu, Jennifer; Nordrehaug, Jan E.; Brodie, Bruce R.; Witzenbichler, Bernhard; Nikolsky, Eugenia; Fahy, Martin; Stone, Gregg W.
<x xml:space="preserve">Abstract</x> Objectives To assess the quality of coronary reperfusion and long‐term clinical outcomes of patients enrolled in the HORIZONS‐AMI trial according to the use of thrombus aspiration (TA). Background The impact of manual TA on microvascular perfusion and clinical outcomes in patients with ST‐segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI) is unsettled. Methods In this retrospective, nonrandomized, subgroup analysis, the authors evaluated thrombolysis in myocardial infarction (TIMI) flow, tissue myocardial perfusion grade (TMPG), ST‐segment resolution (STR), net adverse clinical events (NACE), and major adverse cardiac events (MACE) in patients undergoing pPCI with or without manual TA. Results A total of 318 patients had pPCI with upfront TA, and 2, 917 patients had pPCI without TA. Patients who had TA were more likely to have TIMI 0/1 flow at baseline (75.1% vs. 63.7%, P < 0.0001). There was no difference in the rates of final TIMI 3 flow (90.2% vs. 92.3%, P = 0.19) or dynamic TMPG 2‐3 (77.4% vs. 76.4%, P = 0.68). STR ≥70% was similar in both groups at 60 minutes but higher in the TA group at discharge (71.8% vs. 64.6%, P = 0.02). After multivariable adjustment, TA did not predict MACE at 30 days (HR 0.96 [0.51–1.80], P = 0.90), 1 year (HR 1.03 [0.68–1.55], P = 0.89), or 3 years (HR 1.13 [0.86–1.48], P = 0.39). Stent thrombosis did not differ at 1 year or 3 years. Conclusions In STEMI patients undergoing pPCI, the use of manual TA was associated with improved STR at discharge, but not with any difference in final TIMI flow, TMPG, or MACE. © 2012 Wiley Periodicals, Inc.